AFFECTING FACTORS OF SISTER CITY COOPERATION BETWEEN DENPASAR GOVERNMENT AND MOSSEL BAY GOVERNMENT IN 2019 - I Gusti Agung Made Diah Kencana Putri; Witri Elvianti (Indonesian Journal of International Relations, 2021)
Abstract This study aims to analyze the factors behind the establishment of sister city cooperation between the Denpasar City Government and the Mossel Bay Government since the end of 2019. The author conducted qualitative research to achieve this aim. Thus, this research is expected to enrich other research tools in matters relating to sister city cooperation or paradiplomacy in Indonesia, especially Denpasar. The main data analyzed in this study were obtained through semi-structured interviews with the Head of the Sub-Section for Foreign Cooperation of the Denpasar City in 2020 at the Secretariat of Denpasar. In addition, other types of data that support this research were obtained from the official local government website, several books, journals, reports, and online news sites which reliable and suitable for the content of the research. The focus of this research is to comply with the concept of paradiplomacy and south-south cooperation in identifying the motives behind this sister city cooperation, especially from the side of the Denpasar City Government. As a result, five motives were found that could encourage the Denpasar City Government to accept the sister city cooperation offered by the Mossel Bay Government in 2019, including the international market, tourism and culture, establishing the identity of international partners, the status of government administration, and most importantly, the bilateral relationship between the Indonesian government and the South African government, which in this regards, is an example of the implementation of the South-South Cooperation (SSC) concept. Abstrak Penelitian ini bertujuan untuk menganalisa faktor-faktor yang melatarbelakangi terjalinnya kerjasama sister city antara Pemerintah Kota Denpasar dengan Pemerintah Teluk Mossel pada akhir tahun 2019. Penulis melakukan penelitian kualitatif untuk mencapai tujuan ini. Sehingga, penelitian ini diharapkan dapat memperkaya perangkat penelitian lainnya dalam hal-hal yang berkaitan dengan kerjasama sister city atau paradiplomasi di Indonesia khususnya wilayah Kota Denpasar. Data utama yang dianalisis dalam penelitian ini diperoleh melalui wawancara jenis semi terstruktur dengan Kepala Sub Bagian Kerjasama Luar Negeri Kota Denpasar tahun 2020 di Sekretariat Kota Denpasar. Selain itu, jenis data lain yang mendukung penelitian ini diperoleh dari situs resmi pemerintah daerah, beberapa buku, jurnal, laporan, dan situs berita online yang dapat diandalkan dan sesuai dengan isi penelitian. Fokus penelitian ini adalah menggunakan konsep paradiplomasi dan kerjasama selatan-selatan dalam mengidentifikasi motif dibalik kerjasama sister city ini, khususnya dari sisi Pemerintah Kota Denpasar. Sebagai hasilnya, ditemukan lima motif yang dapat mendorong Pemerintah Kota Denpasar untuk menerima kerjasama sister city yang ditawarkan Pemerintah Teluk Mossel pada tahun 2019 antara lain pasar internasional, pariwisata dan budaya, membentuk identitas mitra internasional, status administrasi pemerintahan, dan yang terpenting, hubungan bilateral antara pemerintah Indonesia dengan pemerintah Afrika Selatan yang dalam hal ini merupakan contoh implementasi konsep Kerjasama Selatan-Selatan (KSS).